Evolution of an evidence-based supermicrosurgery simulation training curriculum: A systematic review. Issue 7 (July 2018) - Pafitanis, Georgios; Narushima, Mitsunaga; Yamamoto, Takumi; Raveendran, Maria; Veljanoski, Damjan; Ghanem, Ali M.; Myers, Simon; Koshima, Isao
Summary: Background: Supermicrosurgery (SM) involves operating on vessels with calibers from 0.3–0.8 mm. SM requires skills beyond those of conventional microsurgery. Current microsurgery courses do not prepare a junior surgeon for such a challenge. Several models have been developed to assist in the early learning curve, but their true purpose, benefit, and validation have not been addressed. This systematic literature review summarizes the existing SM simulation models, and their likely impact on microsurgery training for small-caliber vessel-based procedures is assessed. Methods: An electronic literature search was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. From the literature search, 90 potential articles from MEDLINE and 300 articles from other databases were identified and screened. Twenty-five studies were screened against the inclusion criteria by two independent reviewers for a final critical analysis. Results: Thirty-six articles were included in the reviewing process, and 15 SM simulation training models were identified. The simulation models were classified as nonbiological or biological and as ex vivo or in vivo. None of these models demonstrated validity. However, critical analysis of the full-text articles established the clinical correlation of each model along with the specific skill demonstrated. A novel ladder-based curriculum was established. Further, an expert's questionnaire generated a Likert scale and the clinical impact of each SM simulation training model. Conclusion: This is the first review to highlight the clinical relevance of SM models and the need for validation. Currently, a variety of training models in SM appear to enable the acquisition of specific skills, and the clinical impact of a selection is recognized in a proposed SM simulation training curriculum.